The politics of poverty reduction - Mosley, Paul. (Oxford : Oxford University Press, 2012)
The book focuses on these political processes. Analysis is based partly on global comparisons and partly on case-studies of nine countries that span the developing world. Where governments are politically weak, they need to make alliances with other groups to stay in power, and where these have been with low-income groups, the result may be a lasting and effective pro-poor strategy. Often pro-poor policies have been brought in not with progressive intentions, but out of fear that the state will fall apart unless pro-poor elements are incorporated into government, and the most effective regimes in reducing poverty have seldom been the kindest and most benevolent.
"With assistance from Blessing Chiripanhura, Jean Grugel, and Ben Thirkell-White."
Includes bibliographical references (p. [372]-399) and index.
lje 24/10/17
Loans
Keywords: Poverty; Poverty--Political aspects